Genotypic differences in growth behavior and quality parameters of sugarcane (Saccharum officinarum) varieties under moisture stress conditions - POOJA, POOJA; NANDWAL, A S; CHAND, MEHAR; KUMARI, ANITA; RANI, BABITA; GOEL, VISHAL; SINGH, SAMAR (The Indian Journal of Agricultural Sciences, 2019)
A field experiment was conducted at CCS Haryana Agricultural University, Regional Research Station, Karnal to investigate the effect of available soil moisture regimes on productivity potential of sugarcane (Saccharum officinarum L.) varieties during 2014-15 and 2015-16. The experiment consists of three moisture regimes based on available soil moisture (ASM), i.e. irrigation at 50% ASM (control), 40% ASM (mild stress) and 30% ASM (severe stress) in main plots and four commercial sugarcane varieties differing in maturity duration, i.e. CoS 767 (Mid late), CoH 128 (Mid late), CoJ 64 (Early) and Co 0238 (Early) in sub plot was laid out in split-plot design with three replications. Soil moisture treatments were initiated after 45 days of planting (DAP). Higher germination was recorded in CoJ 64 (65.5%) and CoS 767 (58.0%) as compared to Co 0238 (49.0%) and CoH 128 (48.5%) at 45 DAP. At 30% ASM levels, higher reduction in stalk height was recorded in CoH 128 (33.6 and 85.96 cm) and CoJ 64 (36.33 and 83.03cm) as compared to CoS 767 (41.83 and 107.06 cm) and Co 0238 (50.6 and 122.76 cm) in June and July, respectively. Total number of tillers was reduced by 12.99, 14.37 and 14.5% at 40% ASM level and 16.97, 24.29 and 20.04% at 30% ASM level as compared to irrigation at 50% ASM level in the month of May, June and July, respectively. Significantly higher values of brix, pol and CCS (%) were recorded in CoJ 64 and Co 0238 as compared to CoS 767 and CoH 128 at 8th, 10th and 12th month at all levels of ASM. Varieties and ASM levels had no effect on the specific activity of sucrose synthase. Sugar yield significantly reduced by 31.11 per cent at 40% ASM level and 40.57 per cent at 30% ASM level, respectively as compared to 50% ASM level. Co 0238 and CoS 767 showed minimum reduction in yield than CoH 128 and CoJ 64. From the present study it is concluded that Co 0238 and CoS 767 are identified relatively more tolerant at 30% and 40% ASM levels than CoH 128 and CoJ 64.